Plasma concentrations of tissue kallikrein in normal and preeclamptic pregnancies - Chunyan Yuan; Yuyu Yao; Cong Fu; Tianai Rong; Bing Li; Abdlay Carvalho; Chang Liu (Taylor & Francis Group, 2020)
Objective: To investigate maternal plasma concentrations of tissue kallikrein (TK) in normal and preeclamptic pregnancies. Methods: 96 women with singleton pregnancies were categorized into normal, mild preeclampsia and preeclampsia with severe features. Plasma levels of TK were quantified by ELISA and left lateralrecumbencyposition BP measured. Results: Maternal plasma TK concentrations were significantly lower in preeclampsia with severe features compared with mild preeclampsia and normal pregnant. Plasma TK concentrations were negatively correlated with systolic and diastolic blood pressure, and 24-hour urine protein. Conclusion: Lower maternal plasma TK may be a risk marker that reflects the severity of preeclampsia.